Synthesis and Characterization of New Compounds Derived from N-(mono chloro) Adipoyl Phthalimide - Alrekabi, Zena G (Al-Nahrain Journal of Science, 2019)
This work contain preparation new compounds derived from N-(mono chloro) adip phthalimide (1) in three steps, the first step was prepare Schiff bases compounds from the reaction of N-hydrazino adip phthalimide (2) with different aldehydes and ketones. The second step was prepared thiazolidine ring by the reaction of prepared Schiff bases with mercapto acetic acid. The third step was included preparation of imide ring by react compound (2) with different anhydrides in presence of glacial acetic acid. All the prepared compounds were characterized by FT-IR spectra, some of them by H1-NMR, physical properties and measurements of thermal stability by TG. technique.